The Use Of Learning Journals In Biology Learning Model Design Tools to Improve The Mastery of The Concept of Class XI Science Students SMA Negeri 1 Mejayan. - Andrias Mastanto Setyo Pranoto Andrias Mastanto Setyo Pranoto (ISEJ : Indonesian Science Education Journal, 2020)
This study aims to find out: (1) The use of learning journals in learning biology model design tools to increase motivation and student participation, (2) The use of learning journals in learning biology model design tools to improve mastery of concepts. This research is a collaborative Classroom Action Research conducted in 2 cycles. Each cycle consists of an action planning stage in the form of compiling learning steps with the use of a learning journal in biology learning tool design models, action implementation, observation, and reflection for the next action. The research subjects were students of class XI IPA I in Mejayan State High School in 2018/2019. Data obtained through observation, interviews, questionnaires, document review, and cognitive evaluation tests. Data analysis techniques using qualitative descriptive analysis. Data validation uses the method of triangulation techniques namely tests, questionnaires, and observations. Students' mastery of concepts is measured by tests, questionnaires and observations while motivation and participation are measured by questionnaires and observations. The results of the study show that: (1) Student motivation and participation increases with the use of learning journals in the learning of biology tool design models so as to improve the quality of the learning process, (2) Mastery of student concepts increases with the use of learning journals in learning biology of tool design models. The average percentage of the measurement results of student learning motivation using questionnaires showed an increase of 69.93% in the pre-cycle, the first cycle was 78.55%, and 83.46% in the second cycle which was the final cycle in this study. The average percentage of the measurement results of student learning participation using a questionnaire also showed an increase namely from the pre cycle by 68.46% to 76.04% in the first cycle, and 80.97% at the end of the study. The use of learning journals in biology learning tool design models can improve the quality of learning so that the average percentage of students' mastery of concepts increases from 57.29% in the pre-cycle, to 71.26% in the first cycle and 88.15% at the end of the study.